Reflections of pharmacy students on experiential education in providing health services to people with history of substance use disorders in Malaysia - Mohd Taufek, Nor Hidayah; Halimi, Syafiqah Nadiah; Ab Rahman, Norny Syafinaz; Zin, Che Suraya; Turner, Christopher John (IIUM Press, 2021)
Introduction: Accreditation standards for pharmacy students’ education include the requirement for experiential education (EE) and acknowledge, in building life-long learning skills, the need to develop students’ skills in analysing their practice-based performance. The goal of this qualitative study was to assess students’ ability to reflect on their experience providing face-to-face care to patients with a history of substance use disorders (PHSUDs). Materials and methods: Interviews were conducted with undergraduate pharmacy students who provided care to PHSUDs in an EE programme. An interview guide was used to explore students’ experiences and their perceptions regarding the challenges they encountered, changes in their attitude towards PHSUDs and ways to improve their ability to care for PHSUDs. Data relevant to the study was extracted from interview transcripts,manually sorted and coded using Microsoft Excel and subjected to thematic analysis. Results: The themes identified were 1) Increased self-confidence in face-to-face interactions with PHSUDs 2) Increased empathy towards PHSUDS 3) Reduction in stigmatised attitudes towards PHSUDs 4) Positive nature of the interactions with PHSUDs 5) Appreciation for the opportunity to apply knowledge in practice 6) Recognition of the need for improved communication skill training 7) Recognition of the need to improve training for dealing with unexpected questions and situations. Conclusion: Pharmacy students demonstrated reflective skills in identifying multiple positive learning outcomes stemming from a one-day EE programme involving PHSUDs. In addition, they provided insights useful to faculty in curriculum planning.